2017
DOI: 10.1039/c6cp06276h
|View full text |Cite
|
Sign up to set email alerts
|

First kinetic study of the atmospherically important reactions BrHg˙ + NO2and BrHg˙ + HOO

Abstract: We use computational chemistry to determine the rate constants and product yields for the reactions of BrHg˙ with the atmospherically abundant radicals NO and HOO. The reactants, products, and well-defined transition states are characterized using CCSD(T) with large basis sets. The potential energy profiles for the barrierless addition of HOO and NO to BrHg˙ are characterized using CASPT2 and RHF-CCSDT, and the rate constants are computed as a function of temperature and pressure using variational transition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 85 publications
0
86
0
Order By: Relevance
“…The reaction product of the oxidation of HgBr by NO 2 was computed to be syn-BrHgONO under atmospheric conditions. Because no experimental studies on the reaction of HgBr of NO 2 and HO 2 have been previously reported in the literature, the rate constants computed in this study are significant for future model and laboratory studies [25].…”
Section: Br-initiated Oxidation Of Hgmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction product of the oxidation of HgBr by NO 2 was computed to be syn-BrHgONO under atmospheric conditions. Because no experimental studies on the reaction of HgBr of NO 2 and HO 2 have been previously reported in the literature, the rate constants computed in this study are significant for future model and laboratory studies [25].…”
Section: Br-initiated Oxidation Of Hgmentioning
confidence: 99%
“…The first kinetic study of the reactions of BrHg with NO 2 and HO 2 was recently reported by Jiao and Dibble [25], using computational chemistry. Quantum calculations were performed to obtain the rate constants and product yields for the oxidation reactions of BrHg with NO 2 and HO 2 .…”
Section: Br-initiated Oxidation Of Hgmentioning
confidence: 99%
“…Values of k 0 (T ) and k ∞ (T ) are tabulated by Jiao and Dibble (2017) for different temperatures. At T = {220, 260, 280, 298, 320} K, k 0 NO 2 = {27.4, 13.5, 9.52, 7.10, 5.09} × 10 −29 cm 6 molecule −2 s −1 ; k ∞ NO 2 = {22.…”
Section: Chemical Mechanismmentioning
confidence: 99%
“…This is one area that could potentially be improved in the future. Also, kinetic data for HgBr reactions were updated most recently (Jiao & Dibble, 2017). Due to the limited time frame of the funded project, it was not possible to rerun all the cases in this study.…”
Section: Discussionmentioning
confidence: 99%